Sociabilidades violentas e fé: do tráfico de drogas ao mundo religioso - Lucas, Janaina Correia (2021)
This work aims to analyze the relationship of a group of young people named here by Tram B, linked to a criminal faction in the state of Paraíba with religiosity. As well as the new settings that arise from that relationship. Thus, it seeks to observe the influx of the group within the community, in which it operates in drug trafficking. I intend, from the ethnographic experience, to build a narrative that, respecting certain limits, seeks to understand how the processes that build the ethics of young traffickers are permeated by religious values, become markers that influence social interactions. In the light of the authors who focus on the research on Sociology of Crime and Sociology of Religion, I try to observe the life trajectories of the actors in question, exposing at first the dynamics of the group and the strengthening of ties with the religious world through the approximation with an evangelical church. In this intertwining between crime and religiosity, new forms of itself arise, and the construction of affective bonds. In the second part I will bring the narratives of three women, and the way in which they perceive themselves as mothers of young people inserted in trafficking, as well as the relationship between mother and child in this violent context. Through religiosity, they will be moved from a Christian ethic that implies assiduous participation in meetings. In the third moment, the ritual of mourning experienced by children and mothers at wakes is loaded with meanings, thus, the space of the mourner makes it possible to understand how death is perceived, and it can become a device for actions and senses to guide the subjects at this moment of mourning.